Framework development for English portal for 6 years old / Nurul Huda Nabila Muhammad ... [et al.] - Muhammad, Nurul Huda Nabila; Mohd Mydin, Azlina; Wan Mohammad, Wan Anisha; Johan, Elly Johana; Rosmani, Arifah Fasha (Unit Penerbitan JSKM, 2024)
Since English is a language that is widely utilized in communication on a global scale, speaking English is so important. Through this English portal, students can enhance their English speaking, listening, writing, and reading skills in a controlled and interactive environment. This comprehensive approach strengthens students' language skills while also helping them become more fluent and understanding. The six-year-old "English Portal" system is a ground-breaking and significant early childhood education project. The portal is a groundbreaking and significant effort in early childhood education. Through a smooth integration of learning and fun, the system hopes to completely transform how young students interact with the English language. This project is important because it can provide children with a thorough, engaging, and joyful learning experience that will help develop their foundation in language. With its all-encompassing approach to language instruction, the program plays a critical role in providing students with the tools they need to successfully communicate in a global setting. This E -history application is being developed with the use of the ADDIE approach. A Gantt chart was utilized for this project to forecast the estimated time and ensure that the deadline was met.